Examining the Link Between Sports Tourism, FDI Inflow, Economic Growth, and FDI Inflows: Does Legal Restrictions on Alcohols Consumption During Sports Events Matter? - Ashraf M. A. ELfakharani; Hamza E. Albaheth, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The primary objective of this study is to examine the direct effect of sports tourism, FDI inflows, and legal restrictions on alcohol consumption during sporting events on the economic development of Arab Gulf nations. The study also investigated the moderating effect of alcohol consumption during sporting events on the relationship between sports tourism and economic growth. The panel data methodology and fixed effect are utilized in the study, and GMM estimates are utilized for data analysis. The data for variables from 1995 to 2022 come from the databases of the world bank and national statistical offices. FDI, sports FDI, the organization of mega sports events, alcohol consumption, and sports tourism all appeared to have a positive relationship with economic growth, as indicated by the fixed effect estimates. However, there is no correlation between alcohol consumption and economic growth. The findings of the GMM estimates corroborate those of the fixed effect estimates. Further findings indicate that the relationship between sports tourism and alcohol consumption is positive and statistically significant, which suggests that allowing alcohol consumption in the presence of sports tourism will boost the economic development of Arab Gulf nations. In Arab Gulf countries, where alcohol is frequently regarded as incompatible with religious and cultural values, it is vital to consider the potential cultural and social consequences of alcohol consumption. Therefore, any policy decisions regarding the legality of alcohol consumption in these nations should be thoroughly weighed against other social and cultural concerns. This is one of the first studies to examine the impact of sports tourism, FDI inflows, and legal restrictions on alcohol consumption during sporting events on the economic development of Arab Gulf nations.